La trajectoire des enfants inclus dans la recherche : une expérience en termes de ruptures et de continuités - Solenne Carof (Association Anthropologie Médicale Appliquée au Développement et à la Santé, 2021)
This article explores the consequences for families whose children are included in a research protocol in the context of precision medicine development. While the trajectory of children with advanced cancers is part of a series of bifurcations related to the different therapeutic choices proposed and their organizational consequences, these bifurcations are not necessarily experienced as ruptures by the families. The experience of parents and children is shaped by their understanding of what clinical research is about, but also by the organizational, economic, or emotional resources that allow them to re-establish continuity in a disrupted daily life. This search for continuity persists during the end-of-life phase of the child’s life, even if the child’s death is a major biographical rupture for the whole family.